Global environmental governance, technology and politics the Anthropocene Gap - Galaz, Victor; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2014)
'Victor Galaz opens a new pathway, critically needed, yet breathtaking. In a thoughtful and inspirational manner, he takes on the challenge of how humanity is to navigate the unprecedented scale, speed and complexity of the Anthropocene. The focus is on the interplay between rapid nonlinear global environmental change and emerging technologies, like engineering the planet, tipping points, epidemic surprise or increased connectivity between financial markets, commodity markets, ecosystem services and underlying technologies. In a truly novel way, Galaz moves governance research to the very front of sustainability science and resilience thinking 'Global Environmental Governance, Technology and Politics' is indeed a groundbreaking contribution, highly recommended!'--Carl Folke, Stockholm University, Sweden. 'The idea of the Anthropocene highlights urgent environmental, health and economic challenges facing humanity. This book shows clearly why shifts in power and governance must be core to our responses, but also that new, creative, multi-scale approaches are needed. Candid, reflective and richly-illustrated, this is a must-read contribution to the debate of our age about how to build sustainable futures.'--Melissa Leach, Institute of Development Studies, Sussex, UK. 'The planetary boundaries concept has generated wide discussion and debate, from the research community through to the institution and governance communities that seek to implement the concept. This book fills a very important gap in the discourse. It integrates the basic science that underpins the concept and the innovative approaches that governance researchers and practitioners are applying, to put planetary boundaries into practice. The book's strengths are its excellent description of the science itself, its deft use of that science to inform the development of governance approaches and its application of state-of-the-art research on institutions. I can highly recommend this book for anyone who wants to get beyond the often shallow commentary on and criticisms of the planetary boundaries concept to a much deeper, thought-provoking and insightful analysis of how societies can continue to develop and thrive within the planet's safe operating space.'--Will Steffen, The Australian National University. ''Global Environmental Governance, Technology and Politics' should top the reading list for anyone interested in exploring the nature of governance and the role of technology in this new human-dominated epoch known as the Anthropocene. Combining insights from complexity, innovation and institutional design, Galaz brings cutting edge research to enlighten the current challenges facing humankind. This is a must read.'--Michael Schoon, Arizona State University, US. We live on an increasingly human-dominated planet. Our impact on the Earth has become so huge that researchers now suggest that it merits its own geological epoch - the 'Anthropocene' - the age of humans. Combining theory development and case studies of 'planetary boundaries', emerging infectious diseases, financial markets and geoengineering, this groundbreaking book explores the 'Anthropocene Gap' otherwise known as society's current failure to address the most profound environmental challenges of our times. What are the political and institutional implications of this new epoch? And what are some novel ways to analyse the complicated interplay between institutions, Earth system complexity and technology? This book offers one of the first explorations of political and institutional dimensions of the Anthropocene concept by providing a novel combination of institutional analysis along with insights from Earth system sciences. It provides an exploration of the role of technology for global environmental governance and defines a new agenda for political science analysis in the Anthropocene. Offering the first summary of the planetary boundaries debate, this cutting edge book will be of great interest to researchers concerned in the interplay between politics, technology, and global environmental change, and those interested in the debate surrounding the Anthropocene and "planetary boundaries".
1. Planetary terra incognita -- 2. Complexity and connectedness -- 3. Earth system complexity -- 4. Epidemics and supernetworks -- 5. Engineering the planet -- 6. Financial markets, robots and ecosystems -- 7. Bridging the 'Anthropocene Gap'.
Includes bibliographical references.
Keywords: Global environmental change; Environmental policy -- International cooperation; Electronic books